The impact of problem based learning with google sites on mathematics learning outcomes - Sopwan Muhamad Pakih; Indria Maulani (IKIP Siliwangi, 2026)
Mathematics learning outcomes remain an important concern in the learning process. However, in practice, many students still face difficulties, especially with the Pythagorean Theorem. These difficulties are generally related to a lack of conceptual understanding, inaccuracy in applying formulas, and difficulties in simplifying root forms. This study aims to examine the effect of Google Sites-assisted Problem-Based Learning (PBL) on learning outcomes for the Pythagorean Theorem. A quantitative approach with a one-group pretest-posttest design was used in this study, involving eighth-grade students at SMPN 3 Cikalong Wetan in the 2023/2024 academic year. One class was selected using saturated sampling. Data were collected through tests on learning outcomes of the Pythagorean theorem and questionnaires on students' interest in learning. The data were processed using a paired sample t-test, while the questionnaire data were analyzed based on descriptive statistics. The analysis results showed a significance value of 0.001, so that in a one-tailed test of 0.0005 (< 0.05) with a t-value of –19.426. These results indicate a significant effect on students' mathematics learning outcomes after the application of this learning model. In addition, students' learning interest was in the good category. The findings of this study indicate that the application of Google Sites-assisted Problem Based Learning (PBL) has a positive effect on improving learning outcomes in the Pythagorean theorem material.